2021
DOI: 10.3389/fmicb.2021.688695
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Effects on Microbiota and Silage Fermentation of Alfalfa Under Salt Stress

Abstract: This study investigated the fermentation quality of alfalfa grown in different salt stress regions in China. Following the production of silage from the natural fermentation of alfalfa, the interplay between the chemical composition, fermentation characteristics, and microbiome was examined to understand the influence of these factors on the fermentation quality of silage. The alfalfa was cultivated under salt stress with the following: (a) soil content of <1%0 (CK); (b) 1–2%0 (LS); (c) 2–3%0 (MS); (d) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
3
9
0
2
Order By: Relevance
“…The PCA plots further demonstrated that the six alfalfa epiphytic microbial communities were similar before ensiling. Similar to the work of Blajman et al (2020) and Lu et al (2021) , the abundance and diversity of the bacterial community decreased after ensiling. During the ensiling process, aerobic bacteria and partly aerobic bacteria rapidly consume oxygen in the environment and create an anaerobic environment, causing inhibited metabolic activities of many microorganisms in the raw material and eventually replaced by anaerobic or facultative anaerobic bacteria such as lactic acid bacteria ( Muck et al, 2018 ).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The PCA plots further demonstrated that the six alfalfa epiphytic microbial communities were similar before ensiling. Similar to the work of Blajman et al (2020) and Lu et al (2021) , the abundance and diversity of the bacterial community decreased after ensiling. During the ensiling process, aerobic bacteria and partly aerobic bacteria rapidly consume oxygen in the environment and create an anaerobic environment, causing inhibited metabolic activities of many microorganisms in the raw material and eventually replaced by anaerobic or facultative anaerobic bacteria such as lactic acid bacteria ( Muck et al, 2018 ).…”
Section: Discussionsupporting
confidence: 73%
“…However, in the present study, BA was not detected in the silages in both WL and XJD groups. This suggested the involvement of other bacteria in protein degradation, such as Mycobacterium , Enterococcus and Weissella ( Lu et al, 2021 ; Bao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites. The fecal samples were taken for 16 s rRNA sequencing as described previously [28]. Microbial DNA was extracted and purified using QIAamp DNA Mini Kit, and then PCR amplification was carried out in the V3-V4 hypervariable region of 16 s rRNA gene.…”
Section: Analysis Of Gm and Theirmentioning
confidence: 99%
“…In order to analyze the fermentation characteristics of forage, 10 g samples of silage were combined with 90 g of deionized water and kept in a 4°C fridge for 24 h (Lu et al, 2021). The liquid extract was filtered using four layers of gauze and filter paper and used for the following analysis.…”
Section: Analysis Of Chemical Profile and Fermentation Productsmentioning
confidence: 99%